University Tutoring as A Catalyst in the Training Process of Students in A Peruvian University - Sifuentes, Lucia Guadalupe Panta; Troncoso, Alberto Samuel Monzon; Pittman, Quintter Larry Salas; Apaza-Panca, Cynthia Milagros (Journal of Ecohumanism, 2025)
The purpose of this research was to determine the influence of university tutoring on the educational process of students at a Peruvian university. A model was used that seeks to identify key areas of university tutoring, such as personal development, academic guidance, and career counseling to promote the adoption of positive practices, reduce disparities, and increase effectiveness in the educational process. A study with a quantitative approach, applied, explanatory, was developed with a population of 131 enrolled students and a sample of 100 students, to whom a survey questionnaire of 18 items measured on a Likert-type scale was applied and the data analysis was developed. using partial least squares (PLS) regression. The study determined that university tutoring is explained in 57.7% based on the components academic orientation, personal development and professional advice (R2=0.577) and the student's training process is explained in 95.8% based on tutoring. university (R2=0.958). Additionally, the personal development and professional advice component significantly influences university tutoring, and this significantly influences the student's educational process, for the development of their professional skills. However, the statistical test showed that academic orientation is not significant in university tutoring, but not exclusive either. In this context, tutoring is constituted as an essential component of the training process, transcending the simple transmission of knowledge and focusing mainly on actions that promote the personal development and preparation for the student's professional life.